Review of Economic Stimulus Packages to Fight the Covid-19 Pandemic: Evidence from Malaysia - Mehmood, Waqas; Mohd-Rashid, Rasidah; Aman-Ullah, Attia; Shafique, Owais (South Asian Journal of Social Sciences and Humanities, 2021)
The purpose of this study is to describe the COVID-19 situation in Malaysia and the way the government of Malaysia manages the impact of this pandemic through economic recovery packages such as economic stimulus packages. This study focuses on the effects of the economic stimulus packages released by the government of Malaysia as a response to the economic recession triggered by COVID-19. Malaysia is one of the favourite tourist destinations, and the tourism industry generates about 5.9% of the country’s GDP. However, the lockdown imposed by the Malaysian government to combat the COVID-19 pandemic has severely affected almost every sector of the economy. The Malaysian government has taken several steps to control the spread of the pandemic, such as declaring hotspots of COVID-19, imposing lockdowns, and creating mass scale awareness through social media and TV channels. The government has also deployed several economic strategies such as economic stimulus packages to help industries and the people. This study concludes that the mitigation techniques, i.e., economic stimulus packages adopted are working properly; however, some improvements are required as these techniques are inadequate to manage the transmission capability and virulence of COVID-19. Thus, more attention is required for the revival of economic activities. This study helps to obtain an insight into the effects of economic packages and how effective these packages have been in managing the spread of the COVID-19 virus and mitigating the economic recession. It also provides an understanding of how these packages will help flatten the pandemic curve in the future. This study provides information on the current COVID-19 situation in Malaysia. It also offers information on the policies and methods used by the government to solve economic and public health issues. Further, this study lays out guidelines for policymakers and government officials for the development of more effective strategies for economic recovery and public health initiatives.